Strategija Ekonomsko-poslovne fakultete Univerze v Mariboru 2022–2030 (University of Maribor Press, 2023)
Strategy of the Faculty of Economics and Business of the University of Maribor 2022-2030. The strategy of the Faculty of Economics and Business of the University of Maribor is based on the mission of the Faculty, as well as the many advantages, knowledge and experience of its employees and students, who, in cooperation with the business environment, have created a tradition of excellent economic and business education over a period of more than sixty years. The Faculty’s strategic orientations focus on the opportunities brought by the modern, rapidly changing environment, which is becoming digital in all dimensions, while at the same time we prioritize socially responsible operations and sustainable development. In doing so, we maintain our core values and ethical principles, on which all our operations are based.